The enhanced serotonin (5-HT) synthesis and anti-oxidative roles of Trp oligopeptide in combating anxious depression C57BL/6 mice. (April 2020) - Zhu, Xiping; Sun-Waterhouse, Dongxiao; Tao, Qian; Li, Wenzhi; Shu, Danyang; Cui, Chun
Graphical abstract: Highlights: This study supports Trp oligopeptide for the amelioration of anxious depression. Trp oligopeptide diets actually increases hippocampus and hypothalamic 5-HT levels. The anti-anxious/depression effect may mediate through Trp catabolism and anti-oxidation. Trp oligopeptide normalizes HPA axis hormones, promotes BDNF/TrkB signaling. Abstract: This study compared enhanced serotonin (5-HT) synthesis roles of γ -[Glu]n-Trp (EW) and whey protein hydrolysate (WPH, Val-Ala-Gly-Thr-Trp-Tyr, Val-Ala-Gly-Thr-Trp, Ser-Ala-Trp-Tyr, Trp-Tyr-Ser, Gly-Thr-Trp) using anxious depression C57BL/6 mice. As an index of serotonergic activity, we assessed 5-HT levels in response to Trp oligopeptide ingestion. The neuroprotective and hypothalamic-pituitaryadrenal (HPA) axis hormones were examined in order to characterize the suggested improvements of anxious depression observed in mice after ingestion Trp oligopeptide. The 5-HT levels were increasingly enhanced by the EW and WPH diet, with the EW being more effective. But WPH had higher capacity on anti-oxidative than EW. EW and WPH could normalize the levels of HPA axis hormones, and promote brain-derived neurotrophic factor (BDNF)/tyrosine kinase B (TrkB) signaling. In conclusion, Trp oligopeptide ingestion neuroprotective and HPA regulation effects possibly related to serotonergic activation and anti-oxidation. Consumed Trp oligopeptide diets may induce beneficial effects on anxious depression.